Digital SIBI Non-Textbooks for Color Vocabulary in First-Grade EFL : Usage, Challenges, and Teacher Strategies - Luthfi Dhiyaul Auliyah; Honest Ummi Kaltsum (Jurnal Pendidikan (Teori dan Praktik), 2026)
This study aims to (1) describe the use of the SIBI non-textbook, Luna's Red Seeds, in teaching English reading for first-grade students at SDN Suruh 02, Semarang Regency, (2) identify obstacles that arise during its use, and (3) explore teacher strategies in overcoming these obstacles. This study uses a descriptive qualitative approach, with data collection through observation, interviews, and documentation. Data were analyzed using the Miles, Huberman, and Saldana model, an interactive model of data analysis that has 3 components: data reduction, data presentation, and conclusion drawing. Data validity was maintained through triangulation of sources and techniques, including cross-checking of data from observations, teacher interviews, and learning documents. The results show that the SIBI non-textbook supports student engagement and understanding of color vocabulary through a multimodal learning experience that combines visuals, narratives, and direct interaction. Obstacles that emerged included difficulty matching printed and digital book pages, limited color variations, phonological challenges, and technical problems, which teachers successfully overcome through adaptive strategies, additional media, and learning scaffolding. Overall, Luna's Red Seeds has proven to be a relevant learning medium and supports early English literacy, especially in classrooms with limited resources, as well as providing opportunities for the development of digital learning that can be applied in various contexts and is easily accessible.